Academic-Māori-Woman: The Impossible May Take a Little Longer - Stewart, GT (Informa UK Limited, 2021)
This year’s Waitangi Day, 6 February 2021, saw the revival of a favourite zombie in New Zealand politics when Judith Collins, the leader of the Opposition, complained about not getting a chance to speak during the formalities, calling out Māori culture as sexist i.e. unlawful and backward. Only days earlier, after 25 years of waiting, hearings had finally begun for the ‘urgent’ Mana Wahine claim against the Crown, lodged with the Waitangi Tribunal in July 1993. At the same time, in several places around the country, Māori academics are in public conflict with their employer institutions, and as would be expected, Māori women academics are among those leading these actions. This editorial digs below the surface to identify and briefly sketch the common ground that draws together these various topical threads.